Labour Force Participation of Mature Age Men in Australia: The Role of Spousal Participation - Kostas G. Mavromaras; Rong Zhu (Institute for the Study of Labor (IZA), 2013)
In this paper we estimate the interdependence of labour force participation decisions made by Australian couples from 2001 to 2011. We focus on couples with a mature age husband, and estimate the interdependence of the participation decision of the couple. We find that the decision of a wife to work or not influences positively, and in a causal fashion, the decision of her husband to work or not. In our paper we use counterfactual analysis to estimate the impact of the increasing labour force participation of a wife on her husband's participation. We find that the increased labour force participation of married women observed between 2002 and 2011 has been responsible for about a 4 percentage points increase in the participation of their mature age husbands.
Keywords: J14; J21; 330; labour force participation; spousal status; joint decision making; male employment trends; Australia